Proclus and the Chaldean oracles : a study on Proclean exegesis, with a translation and commentary of Proclus' Treatise on Chaldean philosophy /: a study on Proclean exegesis, with a translation and commentary of Proclus' Treatise on Chaldean philosophy. (2020) - Spanu, Nicola
No abstract available